CIVIL REGISTRY OF MINOR TRANSGENDER IN BRAZIL AND SPAIN - Vieira, Tereza Rodrigues; Molins, M. Esperança Ginebra; Almeida, Natália Cilião de (Revista Direitos Sociais e Políticas Públicas (UNIFAFIBE), 2025)
This article aims to reflect on the adequacy of the name and gender in the Civil Registry of the minor transgender in Brazilian law and Spanish law, since the problem seems to be appeased only with regard to the transgender person of legal age and capable. Spain is slightly ahead of Brazil in this matter, as it already has a constitutional decision in favor of the smallest transgender, however, both countries still do not present rules applicable to these individuals, nor does it have pacification in the judiciary on the subject. Thus, through qualitative methodology, with an emphasis on bibliographic and normative research, elements are presented to bridge the legislative gap in relation to the smallest transgender, in both countries, aiming to alleviate the arduous and slow march of these individuals to ensure the adequacy of the first name and gender, justifying the present study. In this perspective, preventing the desired adequacy may constitute a restriction of their fundamental rights, in addition to preventing the free development of the minor's personality according to their gender.